Interference mitigation through reverse frequency allocation in multi-tier cellular network: a downlink perspective - Jacob, Ponnu (2016)
With the introduction of third generation mobile services, femtocells are considered as an economically feasible solution for combining mobile and internet technologies, thereby giving fast and reliable access to data with a better coverage. However, it is well-known that the femtocells and macrocells sharing the same licensed frequency spectrum results in heavy cross-tier interference which degrades the downlink performance considerably. In this paper, we investigate a novel frequency–division duplex allocation strategy which eliminates the downlink cross-tier interference to the femtocell network from the macrocell base station throughout its coverage area. The proposed scheme seamlessly embed the femtocells within a macrocell resource network to create a heterogeneous two-tier system. It makes use of a cross-tier complementary spectrum sharing technique known as reverse frequency allocation (RFA) where the frequency carriers used in the macrocell transmission are reversed and allocated to femtocells. As a result, it better balances the requirement of greater inter-cell orthogonality and reduced inter-cell interference since macrocell and femtocell operates on different bands in uplink and downlink. It also assures enhanced spectral efficiency and the well-known benefit of reduced outage probability, especially for cell-edge users. This work further analytically quantifies and highlights through simulation results that RFA guarantees greater overall network throughput in the downlink and reduced cross-tier interference regardless of the positioning of the femtocell with respect to the macrocell base station. Also it is to be noted that, with recent academic surveys illuminating that the benefit of femtocells is reflected more in downlink, the focus of the current work is on downlink transmission where the traffic is high and the deployment is more beneficial.